Some Consequences of the Early Twentieth Century Divorce of Ownership from Control - James Foreman-Peck; Leslie Hannah (European Historical Economics Society (EHES), 2012)
Because ownership was already more divorced from control in the largest stock market of 1911 (London) than in the largest stock market of 1995 (New York), the consequences for the economy, for good or ill, could have been considerable. Using a large sample of quoted companies with capital of 1 million or more, we show that this separation did not generally operate against shareholders' interests, despite the very substantial potential for agency problems. More directors were apparently preferable to fewer over a considerable range, as far as their influence on company share price and return on equity was concerned: company directors were not simply ornamental. A greater number of shareholders was more in shareholders' interest than a smaller, despite the enhanced difficulties of coordinating shareholder 'voice'. A larger share of votes controlled by the Board combined with greater Board share ownership was also on average consistent with a greater return on equity. Corporate governance thus appears to have been well adapted to the circumstances of the Edwardian company capital market. Hence the reduction in the cost of capital for such a large proportion of British business conferred a substantial advantage on the economy.
Keywords: G32; G34; L25; 330; corporate governance; company directors; shareholders; board voting control; directors' shareholdings; corporate performance